We, the Nation. Poland and Poles in the Millennium Programme of Primate Stefan Wyszyński (1956-1966/1967) - Bartłomiej Noszczak (Studia Theologica Varsaviensia)
The aim of the Millennium Programme of Primate Wyszyński was to prepare Poles for the millennium of baptism of their country. Social issues have taken an important place in this project. The primate, referring to the problems connected with the life of Poles, emphasised the importance of the transcendental element. He taught that the future of a nation depends on personal involvement in „working on oneself”. He pointed to the national drawbacks of Poles, and then he taught how to get rid of them. In the 1966 jubilee year he repeatedly referred to what Poland is for him and who Poles are in the second millennium of their Christianity. A characteristic feature of this vision was the conviction of the exceptional significance of the Polish nation, which – devoted to the Motherly slavery of Mary – was to continue to work in order to remain semper fidelis regardless of the circumstances.